From Smoking to Vaping: What does Judaism have to Say? - Turner, Akiva (Journal of Public Health International, 2020)
The author reviews rabbinic decisions about smoking from a historical perspective along with the positions of the medical community. The author then brings the current, though limited, rabbinic considerations about vaping given the current state of science, as well as possible discussions for the future, as more becomes known about the safety and health risks associated with vaping.
Keywords: E-cigarettes; vaping; smoking; Judaism; halacha